2012
DOI: 10.1590/s1677-32252012000400004
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with the use of herbal medicines for oral problems by patients attending the clinics of the School of Dentistry, Federal University of Juiz de Fora, Brazil

Abstract: Factors associated with the use of herbal medicines for oral problems by patients attending the clinics of the School of Dentistry,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 18 publications
0
6
0
1
Order By: Relevance
“…The literature indicated the use of Aroeira (Schinus terebinthifolius Raddi or Myracrodruon urundeuva Allemao), whether its stem bark or leaves, for antiseptic, anti-inflammatory, healing, and antimicrobial purposes, mainly in the fight against candidiasis, in addition to being an analgesic, as reported in this study 4 . Other plants cited in the literature for dental pain are mint (Mentha piperita L.) and chamomile (Matricaria chamomilla L. or Matricaria recutita L); however, these substances were not reported in this study 1,3,7 .…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…The literature indicated the use of Aroeira (Schinus terebinthifolius Raddi or Myracrodruon urundeuva Allemao), whether its stem bark or leaves, for antiseptic, anti-inflammatory, healing, and antimicrobial purposes, mainly in the fight against candidiasis, in addition to being an analgesic, as reported in this study 4 . Other plants cited in the literature for dental pain are mint (Mentha piperita L.) and chamomile (Matricaria chamomilla L. or Matricaria recutita L); however, these substances were not reported in this study 1,3,7 .…”
Section: Discussionmentioning
confidence: 65%
“…The use of plants by indigenous people to treat various health conditions has been reported since 6,000 BC in the Indian subcontinent 17 . It is estimated that approximately 80% of the world's civilization uses herbs in primary health care, which emphasizes the need to include herbal medicines in the public health system, as recommended by the World Health Organization (WHO) since the Alma-Ata Declaration in 1978 7 . In this study, which was carried out on a Brazilian indigenous population, it was observed that plant knowledge could be used to treat different oral diseases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fazendo-se uma comparação entre os fitoterápicos / plantas medicinais citados pelos Cirurgiões-Dentistas entrevistados e aqueles que a literatura descreve como utilizados por profissionais da saúde, podem-se identificar o Maracujá (Passiflora edulis), utilizado como efeito calmante 4,17 ; a Romã (Punica granatum), utilizada como efeito antimicrobiano 4,14,18 ; a Folha de Batata (Ipomoea batatas), utilizada para dor, inflamação, infecção e edema 19 ; a Transagem (Plantago major L.), utilizada para dor, edema e inflamação 19 ; a Folha de Algodão (Gossypium hirsutum L.), utilizada para infecção e dor 19 , e a Camomila (Matricaria chamomilla), utilizada para dor 19 e ansiolítico 17 .…”
Section: Materials E Métodounclassified